Colour contrast enhancement based on bright and dark stretching for Ziehl-Neelsen slide images - Zaleha, Salleh (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org